Influence of electronic factors on pd-mediated cycloisomerization: a systematic investigation of competitive 6-exo-dig versus 7-endo-dig cyclizations of sugar alkynols - Ramana, C. V.; Induvadana, Boddeti; Srinivas, Burgula; Yadagiri, Kommagalla; Deshmukh, Madhusudhan N.; Gonnade, Rajesh G. (Tetrahedron, 2009)
Pd-mediated cycloisomerization of 3-C-propargyl-ribo- and allofuranose derivatives was investigated in detail to understand the influence of electronic factors on the regioselectivity (6-exo- vs 7-endo) of alkynol cycloisomerization leading either to a six- or seven-membered ring. In general, the 6-exo-dig mode of cyclization is facile and is independent of electronic factors. With some of the alkynols, a regioselective (7-endo?) hydration of the alkyne unit was observed and this has been attributed to the participation of C(3)-OH. When the C(3)-OH was protected as its benzyl ether, cycloisomerization of these alkynols occurred exclusively in a 6-exo-dig mode resulting in the corresponding [3.2.1]-bicyclic ketals. Additional control experiments conducted were in support of the participation of C(3)-OH in regioselective alkyne hydration. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Alkynol cycloisomerization; Bridged bicyclic ketal; Palladium; Sonogashira coupling; Sugar alkynol